Yoga Exercise Effectively Reduces Dysmenorrhea In Adolescent Girls At Budi Murni 2 Private High School Medan - Indarsita, Dina; Yufdel, Yufdel; Batubara, Dahlia Fronika (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Background: Dysmenorrhea is a common menstrual problem among adolescent girls and often affects daily activities, concentration, and academic performance. Yoga exercise is known to reduce menstrual pain through relaxation, improved blood circulation, and increased endorphin release. This study aimed to analyze the effectiveness of yoga exercise in reducing dysmenorrhea among adolescent girls at Budi Murni 2 Private High School Medan. Methods: This pre-experimental study employed a one-group pretest– posttest design involving 56 adolescent girls selected using purposive sampling. Yoga exercise was conducted for 30 minutes twice weekly. Dysmenorrhea intensity was assessed using the Wong Baker Faces Pain Rating Scale before and after the intervention. Data were analyzed using descriptive statistics and the Spearman Rank correlation test. Results: Before the intervention, 82.1% of respondents experienced severe dysmenorrhea. After yoga exercise, 85.7% reported a decrease to mild pain, and 12.5% reported no pain. The Spearman Rank correlation test showed a significant relationship between yoga exercise and dysmenorrhea reduction (p = 0.019) with a very strong negative correlation (r = –0.885). Conclusion: Yoga exercise is effective in reducing dysmenorrhea among adolescent girls. The findings support yoga as a non-pharmacological intervention that can be integrated into school-based health programs to manage menstrual pain.